Beyond destruction: emerging roles of the E3 ubiquitin ligase Hakai - Juan-José Escuder-Rodríguez; Andrea Rodríguez-Alonso; Lía Jove; Macarena Quiroga; Gloria Alfonsín; Angélica Figueroa (Cellular & Molecular Biology Letters)
Abstract Hakai protein (CBLL1 gene) was identified as an E3 ubiquitin ligase of E-cadherin complex, inducing its ubiquitination and degradation, thus inducing epithelial-to-mesenchymal transition. Most of the knowledge about the protein was associated to its E3 ubiquitin ligase canonical role. However, important recent published research has highlighted the noncanonical role of Hakai, independent of its E3 ubiquitin ligase activity, underscoring its involvement in the N 6-methyladenosine (m6A) writer complex and its impact on the methylation of RNA. The involvement of Hakai in this mRNA modification process has renewed the relevance of this protein as an important contributor in cancer. Moreover, Hakai potential as a cancer biomarker and its prognostic value in malignant disease also emphasize its untapped potential in precision medicine, which would also be discussed in detail in our review. The development of the first small-molecule inhibitor that targets its atypical substrate binding domain is a promising step that could eventually lead to patient benefit, and we would cover its discovery and ongoing efforts toward its use in clinic. Graphical Abstract